GOST 8.315 "GSI. Reference materials of composition and properties of substances and materials. Basic concepts": basic principles of revision - E. V. Osintseva (Стандартные образцы)
A key point of the revision of GOST 8.315"GSI. Reference materials of composition and properties of substances and materials. Basic concepts" is harmonization with the documents of International Organization for Standardization (ISO) and International Organization of Legal Metrology"(OIML) in terms of reference materials. The article sets out the basic principles of the document revision: harmonization of terms and definitions with ISO Guide 30:2015, distinction between "reference material" and "certified reference material" not only as concepts, but also as objects, which are subject to their own requirements and criteria of development, production and use (according to ISO Guide 31, ISO Guide 35, ISO 17034); introduction ofprovisions, related to the issue of reference materials, accredited to ISO 17034 by RM producers; introduction of provisions in the area of legal metrology in terms of reference materials according to OIML D 18. Introduction of the updated document will contribute to a new round of RM activity in Russia and other member-countries of Interstate council, based on international principles of RM development and use.